Barriers to Adherence to Iron Chelation Therapy in Thalassemia Patients - Barua, Tanuka; Tayab Ali, Golam Mohammed; Chowdhury, Rana; Das, Dhananjoy; Chowdhury, Showrov Barua; Chowdhury Arzu, Mahmud Ahmed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Thalassemias are the most common inheritable blood disorders requiring regular blood transfusions and iron chelating therapy. Non-adherence to iron chelation therapy increases complications and is a problem in treating thalassemia. To assess the reasons of non-adherence to iron chelating drug in treating thalassemia. Materials and methods: This descriptive cross-sectional study was carried out in the thalassemia ward of Chattogram Maa Shishu-O-General Hospital, Chattogram from July, 2013 to June, 2014. 70 thalassemia patients aged 2-18 years previously treated with iron chelating drugs were included. Parents were interviewed according to a formulated questionnaire based on discontinuation of iron chelating drugs and its reasons. Data were analyzed by both manually and by SPSS-18. Results: About 48.6% patients needed blood transfusion >10 units/year and 62.9% patients were prescribed with iron chelating drugs. Near about half patients (47.7%) did not continued iron chelating therapy till full prescribed period. Deferiprone (31.8%) and combination of deferipronc & desferrioxamine (31.8%) was the most commonly prescribed drug. Deferiprone is the drug to which most of the patients (70%) were adherent and a good number of patients (65%) discontinued desferrioxamine. Financial problem (100%) was the only reason for discontinuation of oral chelator. In case of parenteral chelator, besides finanacial problem (38.5%), time consuming natures (38.5%), need of hospital admission (23%) are the other causes for non-adherence to iron chelation therapy. Conclusion: Financial problem is the main cause of non-adherence to iron chelation therapy. Iron chelating drugs should be available at low cost. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 45-49